Analisis Tipe Kepemimpinan dalam Film “The Last Samurai” - Vigor Wirayodha Hendriwinaya (Buletin Psikologi, 2016)
This paper displays an analysis of several literature reviews. It aims to understand the types of leadership depicted in the characters of the “Last Samurai” movie. The dilemma of cultural, political, economic and military transition for Japan in approaching the modern era is an exciting scenario depicted in the “The Last Samurai” movie. Having leaders compete against each other in achieving their intended goals, made it easy for the audience to analyze their type of leadership. The types of leadership from old to modern Japan t hat competes with Western countries is shown in this movie, particularly regarding its’ effectiveness and relevance. The visionary leadership is represented by Omura, an advisor who influenced the Emperor in realizing the comparative and competitive value of the Japanese people, allowing them to compete with various innovations and develop along with the challenges of the era. The "Wisdom and Charismatic" leadership type was present in Katsumoto, the Samurai leader and Emperor's teacher who wanted to maint ain the noble values of Japanese culture. Katsumoto's exemplary leadership is reflected in his extraordinary devotion, heroism, character, and his firm adherence to the command given to him as a samurai. Such traits inspire awe, respect, and devotion from a group of samurai. An overview of the Visionary leadership type, "Wisdom and Charismatic" encountered in the figures of Omura and Katsumoto. Today's challenges require each member to be innovative, creative, competitive, competent, and brave enough to tak e risk. In achieving that vision, leaders with charismatic soul are needed